THE LOCAL WISDOM OF KEI PEOPLE AS A SOURCE OF LEARNING LOCAL HISTORY TO STRENGTHEN STUDENTS’ SOCIAL COHESION - Ulfie, Agustinus (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
Local culture as a social capital in the life of Kei people should always be established particularly for young generation through education. Now the Kei People is being introduced by modern culture as a reflection of city life, it tends to precede individualistic as well as materialistic which affect the occurrence of violence, brawling or gang fighting, hoodlumism, and even terrorism which have degraded moral values of nation. Conserving values of culture as the local wisdom of Kei people is very important not only to control violence, brawling or gang fight between groups, individualism, and hedonism which have been dominating the local people life, but also because this region have ever been stricken by social conflicts. Rebuilding as well as retighten social solidarity and cohesion through learning history sourced from values of local wisdom are indeed required. Social Cohesion is an adhesive uniting society, developing sociological harmony and spirit along with commitment to achieve mutual goals. Reviving and conserving values of local culture which are applied as a source of learning local history are absolutely imperative in order to eliminate even stop various violence, revive conflict, brawling or gang fight, and drugs abuse among young generation.